Produção de hidrogênio em reator anaeróbio de leito fluidizado a partir de glicerol bruto sob condições termofílicas - Ferreira, Janaína dos Santos (2014)
This study aimed to evaluate the influence of the hydraulic retention time (HRT) on hydrogen production using crude glycerol as a substrate in an anaerobic fluidized bed reactor (AFBR ) . The reactor had a volume of 1979 cm3, which was varied HDT in eight stages: Stage I, II, III, IV, V, VI , VII, VIII with HDT of 14, 12 , 10,8 , 6, 4 , 2 and 1 hour. The temperature was controlled at 55 °C, fixing the substrate concentration in the amount of 5 gL -1 . The inoculum used was granular sludge from the thermophilic anaerobic reactor and upflow sludge blanket ( UASB ) for the treatment of vinasse, located at Usina São Martinho , Pradópolis - SP . The results showed that the yield of hydrogen (HY) remained constant between the HDT of 2h to 14h (1.2 H2.mol glycerol and 1.4 mol -1) HRT of 1h and the yield was higher ( 3 moles H2 . glycerol mol -1). The volumetric H2 production was increased with decreasing HRT , with its maximum value of 1508.7 mL.h - 1.L - 1 in lower applied TDH (1h) . The biogas produced was composed of CO2 and H2. The composition varied with the decrease in HRT from 14 to 2h (Step IVII ) in the first seven stages (14 to 2 h ), reaching a mean rate between 50 and 60%. In the last phase, which HRT was 1h , the percentage of H2 biogas reached the maximum value of 70 % . The major metabolites obtained during the first seven stages of operation of the reactor were: Acetic acid (4.5 to 18%), butyric acid (4.3 to 21% ), ethanol (14 to 29%) and 1,3-propanediol (34 to 50%). As for 1h note the HDT of the presence of propionic acid (56%), acetic acid ( 11.5%) and 1,3- propanediol ( 30%).